Tcf12 Is Involved in Early Cell-Fate Determination and Subset Specification of Midbrain Dopamine Neurons - Mesman, Simone; Smidt, Marten P. (Frontiers in Molecular Neuroscience, 2017)
The basic helix-loop-helix (bHLH) protein family has previously been shown to be involved in the development of mesodiencephalic dopaminergic (mdDA) neurons in the murine midbrain. Specifically, Ngn2 and Mash1 are known to have a role in the specification of neural progenitors in the ventricular zone of the midbrain towards an mdDA neuronal cell-fate. Furthermore, other members of the bHLH protein family, the E-box factors, are expressed in the developing midbrain and are thought to have a role in neuronal differentiation. Here we show that the E-box factor Tcf12 is implicated in early and late development of mdDA neurons. Tcf12 is expressed in the midbrain and in young TH-expressing mdDA neurons throughout development. Tcf12lox/lox;En1cre/+ embryos, that lose Tcf12 at embryonic day (E)9 throughout the En1 expression domain, have a changed spatial expression of Lmx1a and Nurr1 and a consistent loss of rostral TH expression. Expression of the subset marker Ahd2 is initially delayed, but recovers during development, eventually showing an 10% increase in AHD2-expressing cells at postnatal day (P)30. Tcf12lox/lox;Pitx3cre/+ embryos, that lose Tcf12 at E12 in post-mitotic mdDA neurons, show no effect on the amount of TH-expressing neurons in the developing midbrain. However, similar as to Tcf12lox/lox;En1cre/+ embryos, subset specification is delayed during development. Taken together, we have identified Tcf12 as a novel factor in mdDA neuronal development. It serves a dual function; one in early cell-fate commitment of neural progenitors and one late in subset specification.